If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(X+3)=6(X1)X
We move all terms to the left:
4(X+3)-(6(X1)X)=0
determiningTheFunctionDomain 4(X+3)-6X1X=0
We multiply parentheses
4X-6X1X+12=0
We move all terms containing X to the left, all other terms to the right
4X-6X1X=-12
| 4-6(x+4)=2(3x-1)+7x-4 | | u-5=-9 | | 25+5y=60 | | 3p-62=3p-80 | | 18=v/3-8 | | 10=c+ 8 | | 8x-15=24-2x | | 3p-80=3p-62 | | 3/x=-2/5 | | 2y-9=9y-93 | | (x-1)^5=32 | | 34=x/4+9 | | 10=c4+ 8 | | w/6=5/30 | | 34=x/4=9 | | y=-3(-1.5)+2.5. | | -y+245=191 | | 3-0.4(x+2)=7.8+1.1x | | 2y–9=9y–93 | | -12x+4+6x-2=8 | | y=-3(1)+2.5. | | -v+122=230 | | 3x/2+1=-11/2 | | 6b+b-2-2=19 | | 6(4x+7)-4=3x-8 | | 0.25x+0.7x=x-1 | | m+7=+m-4 | | -1.5=-3x+2.5 | | 274-y=166 | | x/88=2 | | x+(3/5)=5(1/2) | | -6x-11=-54 |